Peloidal tempestites of the Vaca Muerta Formation (Tithonian-Valanginian) in the southern Mendoza, Neuquén Basin, Argentina (Latin American Journal of Sedimentology and Basin Analysis, 2021)
Storm deposits (tempestites) have been extensi- vely studied in the sedimentary record, particularly those deposits with hummocky cross-stratification, knowing their bathymetric ranks, facies models and their hydrodynamic conditions (Harms et al., 1975; Dott y Burgeois, 1982; Dumas y Arnott, 2006). However, detailed studies in carbonate sediments are relatively scarce. Recently, other types of interference generated at the picnocline interface (internal waves) were proposed to interpret similar deposits without being controlled by the position of the of storm-wave level (Pomar et al., 2012). The Tithonian - Valanginian deposits in the southern Mendoza - Neuquén Basin are particularly interesting because of their association with a homoclinal carbonate ramp system. During the Late Jurassic - Early Cretaceous a series of marine sequences were developed throughout the basin that are grouped under the Mendoza Group. In the southern Mendoza area it includes the Vaca Muerta Formation (early Tithonian - early Valanginian), the Chachao Formation (early Valanginian) and the Agrio Formation (early Valanginian - early Barremian) (Figs. 1 and 2). The Vaca Muerta Formation is widely distributed over the entire Neuquén Basin. It consists of dark bituminous shales, marls and limestones deposited in response to a rapid and widespread marine transgression originated from the Pacific Ocean, as consequence of a tectonic phase of compressional relaxation (Legarreta and Uliana, 1991). While initial studies show significant variations in the proportions of different lithologies, sedimentological knowledge is still general, with the exception of contributions from the south of the basin (Spalletti et al., 2000, 2008; Scasso et al., 2002, 2005) and southern Men- doza area (Doyle et al., 2005; Kietzmann et al., 2008, 2011). Storm deposits are well developed in the Vaca Muerta Formation. Based on tempestites characteristics and their associated beds four distinct deposits have been identified in the Bardas Blancas area (Fig. 3): (1) packstones with low- angle cross-stratification, (2) packstones/grainstones with large scale hummocky cross-stratification, (3) rudstones/grainstones with small scale hummocky cross-stratification, and (4) laminated wackestones/ packstones with intralaminar normal gradation (Figs. 5 and 6). Packstones with low-angle cross-stratification can be interpreted as anisotropic hummocks deposits or low relief megaripples generated under combined flows during major storms in the middle ramp. A complete sequence of HCS consists of three divisions (Sa-Sc) associated with the storm event, and an upper unit (Sd) that represents the fair- weather period between major storm events. Unit Sa starts with an erosion base and consists in low angle cross-stratified rudstones/grainstones. Unit Sb The unit begins with a second order surface and is composed by packstones and grainstones with hummocky cross-stratification. Unit Sc is represented by peloidal packstones with ripple marks, and finally the unit Sd consists of laminated wackestones/packstones. Laminated wackestones/packstones with intra- laminar normal gradation consist of bioclastic wackestones/packstones composed of saccocomids remains or a rhythmic alternation of peloidal packstones and sandy layers with current ripple marks, which probably represents the distal expression of the storms. Variations from this sequence allow us to make some comparison with other ancient carbonate storm deposits (Kreisa, 1981; Monaco 1992, Sami y Descorchers, 1992; Molina et al., 1997; Zhou et al., 2011). Although deposits of the Vaca Muerta Formation are compositionally similar to those described by Molina et al. (1997), the ideal sequence is similar to that recognized by Monaco (1992) (Fig. 10). The division proposed by Monaco (1992) seems to be the most accurate, since it is based on the recognition of structures generated under different hydrodynamic conditions rather than genetic inter- pretations associated with the phases of the storm. Comparing the described storm-influenced deposits with ancient and modern storm deposits examples, a relative water depth of 25 to 50 m is estimated for the formation of the HCS limestone facies. Even assuming its origin from internal waves, the position of the pycnocline in warm seas and small basins would be found within the same depth range (Nordberg et al., 2000), so that the deposits described in this paper may be important in future palaeogeographical studies in the Neuquén Basin.
Keywords: Tempestites, Carbonate Pseudomatrix, Carbonate Ramp, Jurassic-Cretaceous.